Notes from the Editor-in-Chief - Peggy Leatt (HealthcarePapers, 2011)
As I was reading and thinking about the contributions to this issue of Healthcare Papers focused on collaborative policy making, one of my favourite quotations kept coming to the forefront of my mind: "In the long history of humankind (and animal kind, too) those who learned to collaborate and improvise most effectively have prevailed." If you do a quick search for this uplifting statement online, you will most likely be told that its author is none other than the renowned British scientist Charles Darwin. Alas, dig a little deeper, and you will learn that the attribution of this quotation to the father of evolutionary theory is almost certainly an error (Darwin Correspondence Project 2011). Nobody, it seems, actually has the foggiest who first uttered or inscribed this pithy observation!
Keywords: health policy, policy making, health services research, health services delivery